Impact of advanced footwear technology on elite men`s in the evolution of road race performance - Rodrigo-Carranza, V.; González-Mohíno, F.; Santos-Concejero, J.; González-Ravé, J. M. (Journal of Sports Sciences, 2022)
Advanced footwear technology (AFT) changed footwear design concepts by using a curved carbon fibre plate in combination with new, more compliant and resilient foams. The aim of this study was (1) to examine the individual effects of AFT on the evolution of the main road events and (2) to re-assess the impact of AFT on the world`s top-100 performance in men`s 10k, half-marathon and marathon events. Data from the top-100 men`s 10k, half-marathon and marathon performances were collected between 2015 and 2019. The shoes used by the athletes were identified in 93.1% of the cases by publicly available photographs. Runners wearing AFT had an average performance of 1671 ± 22.28 s compared to 1685 ± 18.97 s of runners not using AFT in 10k (0.83%) (p < 0.001), 3589 ± 29.79 s compared to 3607 ± 30.49 s in half-marathon (0.50%) (p < 0.001) and 7563 ± 86.10 s compared to 7637 ± 72.51 s in the marathon (0.97%) (p < 0.001). Runners wearing AFTs were faster by ~1% in the main road events compared to non-users. Individual analysis showed that ~25% of the runners did not benefit from the use of this type of footwear. The results of this study suggest that AFT has a clear positive impact on running performance in main road events.